N-acetylcysteine negatively regulates Notch3 and its malignant signaling - Zhang, Xiong (Oncotarget, 2016)
Notch3 receptor is expressed in a variety of cancers and the excised active intracellular domain (N3ICD) initiates its signaling cascade. N-acetylcysteine (NAC) as an antioxidant has been implicated in cancer prevention and therapy. In this study, we demonstrated a negative regulation of Notch3 by NAC in cancer cells. HeLa cells treated with NAC exhibited a time- and concentration-dependent decrease in Notch3 levels and its downstream effectors Hes1 and HRT1 in a manner independent of f-secretase or glutathione. In contrast, NAC did not affect protein levels of Notch1, the full length Notch3 precursor, or ectopically expressed N3ICD. Although SOD, catalase and NAC suppressed reactive oxygen species in HeLa cells, the first two antioxidants did not impact on Notch3 levels. While the mRNA expression of Notch3 was not altered by NAC, functional inhibition of lysosome, but not proteasome, blocked the NAC-dependent reduction of Notch3 levels. Furthermore, results from Notch3 silencing and N3ICD overexpression demonstrated that NAC prevented malignant phenotypes through down-regulation of Notch3 protein in multiple cancer cells. In summary, NAC reduces Notch3 levels through lysosome-dependent protein degradation, thereby negatively regulates Notch3 malignant signaling in cancer cells. These results implicate a novel NAC treatment in sensitizing Notch3-expressing tumors.